Substituted thiobenzoic acid S-benzyl esters as potential inhibitors of a snake venom phospholipase A 2: Synthesis, spectroscopic and computational studies (2012)
4-Chlorothiobenzoic acid S-benzyl ester (I), 3-nitrothiobenzoic acid S-benzyl ester (II), 4-nitrothiobenzoic acid S-benzyl ester (III) and 4-methylthiobenzoic acid S-benzyl ester (IV) were prepared and characterized by 1H and 13C NMR, Mass spectrometry and IR spectroscopy. Quantum chemical calculations were performed with Gaussian 09 to calculate the geometric parameters and vibrational spectra. Phospholipase A 2 (PLA 2) was purified from Crotalus durissus cumanensis venom by molecular exclusion chromatography, followed by reverse phase-high performance liquid chromatography. Two studies of the inhibition of phospholipase A 2 activity were performed using phosphatidilcholine and 4-nitro-3-octanoyloxybenzoic acid as substrates, in both cases compound II showed the best inhibitory ability, with 74.89% and 69.91% of inhibition, respectively. Average percentage of inhibition was 52.49%. Molecular docking was carried out with Autodock Vina using as ligands the minimized structures of compounds (I-IV) and as protein PLA 2 (PDB code 2QOG). The results suggest that compounds I-IV could interact with His48 at the active site of PLA 2. In addition, all compounds showed Van der Waals interactions with residues from hydrophobic channel of the enzyme. This interaction would impede normal catalysis cycle of the PLA 2. © 2012 Elsevier B.V. All rights reserved.